The language use Inventory-Persian: report of the psychometric properties - Mahbubeh Nakhshab; Ali Asgary; Akram Ahmadi (BMC Psychology)
Abstract Background Pragmatic language assessment is a necessary component of evaluation in language impairments. Some procedures are applied to assess pragmatic abilities in childhood. Parent-report questionnaires are among the most useful instruments for evaluating pragmatics in real situations. This study aimed to translate and adapt the Language Use Inventory (LUI) into Persian and examine its psychometric properties. Method It was a methodological and cross-sectional study. We pursued the steps of translation and adaptation of this questionnaire into Persian according to a standard guideline. Then, 348 parents/caregivers of three groups of children consisting of typically developing (TD), late-talking children, and ones with autism spectrum disorders (ASD) 18-47-month-old Persian-speaking children completed the adapted version of the LUI. The participants were recruited into study by convenience sampling. Next, different psychometric properties including item analysis, validity (content, face, and construct), and reliability (test-retest and internal consistency) were investigated. Results Translation, adaptation, and item analysis led to the deletion of 7 Items. Differential validity for age revealed the noticeably different performance among different age groups (p < 0.001). Also, Given the clinical validity, TD and ASD children performed differently in this measure(p < 0.001). In addition, the evidence of the discriminant validity was confirmed by a significant difference between TD and late-talking children (p < 0.001). Concurrent validity was also established by a moderate and positive value of the correlation between total scores of the LUI-Persian and Newsha developmental scale (r = 0.54, p = 0.01). Exploratory factor analysis (EFA) indicated that the Language Use Inventory-Persian had 2 factors of verbal and nonverbal use of language. Also, the evidence for the confirmatory factor analysis (CFA) was attained (all the values of factor load were higher than 0.40). The internal consistency (α = 0.99) and test-retest reliability (r = 0.97) proved adequate values. Conclusions The Language Use Inventory-Persian with 173 items revealed the acceptable psychometric attributes for assessing pragmatics in 18-47-month-old Persian-speaking children; however, for screening pragmatic impairments, it may need further studies on clinical populations with a larger sample size to see whether the LUI items are appropriate or possible changes in the items are required.